Determination of The Active Asiaticoside Content in Centella asiatica as Anti-Cellulite Agent - Dewi Sondari; Sri Budi Harmami; M. Ghozali; Ahmad Randy; Athanasia Amanda S.; Yan Irawan (Indonesian Society for Cancer Chemoprevention, 2011)
Centella asiatica accumulates large quantities of pentacyclic triterpenoid saponins, collectively known as centelloids. These terpenoids include asiaticoside, centelloside, madecassoside, brahmoside, brahminoside, thankuniside, sceffoleoside, centellose, asiatic-, brahmic-, centellic- and madecassic acids. Preparations of C. asiatica are used in traditional and alternative medicine due to the wide spectrum of pharmacological activities associated with these secondary metabolites, such as anticellulite agent. Asiaticoside was found in Centella asiatica. In this present study, the asiaticoside was extracted using methanolic and ethanolic solvent. Determination of the asiaticoside content in the extract was conducted with High Performance Liquid Chromatography (HPLC), Thin Layer Chromatography (TLC), and Fourier Transform Infra Red (FTIR). Samples of C. asiatica used in this study came from three different plantation areas, Bogor, Lembang and Solo. Asiaticoside content in the methanolic extract from Bogor, Lembang, and Solo samples were 2.82%; 2.68%; and 2.8% respectively. Asiaticoside in ethanolic extract from Bogor, Lembang, and Solo samples were 2.79%; 2.75%; and 2.91% respectively. Two way ANOVA study showed that there was significant difference between types of solvent used in extraction and the asiaticoside content in the obtained extract, significant difference between varied plantation area and obtained asiaticoside content, and significant difference between interactions of different solvent with different plantation area. Keywords: Centella asiatica, asiaticoside, anticellulite, medicine, metabolites